Mechanistic aspects of asymmetric intramolecular Heck reaction involving dynamic kinetic resolution: flexible conformation of the cyclohexenylidene–benzene system. Issue 15 (15th April 2015) - Hosoi, Shinzo; Ozeki, Minoru; Nakano, Masashi; Arimitsu, Kenji; Kajimoto, Tetsuya; Kojima, Naoto; Iwasaki, Hiroki; Miura, Takuya; Kimura, Hiroyuki; Node, Manabu; Yamashita, Masayuki
Abstract: An asymmetric intramolecular Heck reaction that involves the dynamic kinetic resolution of an atropisomer as the substrate furnished a product in high yield with high enantioselectivity. DFT calculations (Spartan'10, B3LYP/6-31G*) confirmed that the reaction proceeded via atropisomerization involving a conformational transformation (half-chair form/distorted-boat form) of the substrate. Graphical abstract: